Institutional Frameworks of the Development of Non-Government Universities in Russia - НеуважаеваМария Андреевна (Journal of Economic Sociology, 2012)
The paper proposes a critical study focusing on the development of non-government higher education sector in Russia from new institutionalism perspective in economic sociology. Conditions under which private universities spread in other countries are identified. In some countries non-governmental universities successfully complement governmental ones, in some countries private universities displace state universities. Recent research shows that private sector produces some organizational divergences (especially under privatization and emerging liberal markets). However the presented paper argues that Russian case is specific. Governmental and non-governmental universities are initially intertwined. This fact provokes us into thinking about the Russian higher education system from the alternative point of view. Based on in-depth interviews with founders and lecturers from Moscow private universities and the survey of students the paper intends to trace structuration of non-governmental education field and to demonstrate impacts of institutional isomorphism mechanisms on private universities.